Dynamic Quantum Matter (Ann. Phys. 2/2020). Issue 2 (14th February 2020) - Balatsky, Alexander V.; Haraldsen, Jason T.; Black‐Schaffer, Annica M.; Pertsova, Anna; Hofmann, Philip
Abstract : Dynamics play an essential role in the investigation of quantum materials and matter. In this special issue, multiple facets of dynamic quantum matter are investigated and examined. The cover image shows a photon on a Dirac cone, which illustrates the interaction between photons and electrons to produce dynamic states. (Image created by Bart Olsthoorn)